Design, synthesis, and biological evaluation of conformationally constrained glycerol 3-phosphate acyltransferase inhibitors - Wydysh, E.A.; Vadlamudi, A.; Medghalchi, S.M.; Townsend, C.A.
Glycerol 3-phosphate acyltransferase (GPAT)isozymes are central control points for fat synthesis in mammals. Development of inhibitors of these membrane-bound enzymes could lead to an effective treatment for obesity, but is thwarted by an absence of direct structural information. Based on a highly successful study involving conformationally constrained glycerol 3-phosphate analogs functioning as potent glycerol 3-phosphate dehydrogenase inhibitors, several series of cyclic bisubstrate and transition state analogs were designed, synthesized, and tested as GPAT inhibitors. The weaker in vitro inhibitory activity of these compounds compared to a previously described benzoic acid series was then examined in docking experiments with the soluble squash chloroplast GPAT crystal structure. These in silico experiments indicate that cyclopentyl and cyclohexyl scaffolds prepared in this study may be occluded from the enzyme active site by two protein loops that sterically guard the phosphate binding region. In view of these findings, future GPAT inhibitor design will be driven toward compounds based on planar frameworks able to slide between these loops and enter the active site, resulting in improved inhibitory activity.
Keywords: GLYCEROL 3-PHOSPHATE ACYLTRANSFERASE; GPAT; OBESITY; TRIACYLGLYCEROL